Planar Chiral Phosphoramidites with a Paracyclophane Scaffold: Synthesis, Gold(I) Complexes, and Enantioselective Cycloisomerization of Dienynes. Issue 10 (2nd February 2016) - Wu, Zhiyong; Isaac, Kévin; Retailleau, Pascal; Betzer, Jean‐François; Voituriez, Arnaud; Marinetti, Angela
Abstract: The key structural feature of the new phosphoramidites is a paracyclophane scaffold in which two aryl rings are tethered by both a 1, 8‐biphenylene unit and a O−P−O bridge. Suitable aryl substituents generate planar chirality. The corresponding gold(I) complexes promote the cycloisomerization of prochiral nitrogen‐tethered dienynes. These reactions afford bicyclo[4.1.0]heptene derivatives displaying three contiguous stereogenic centers, with very high diastereoselectivity and up to 95 % ee . Abstract : The key structural feature of the new phosphoramidites is a paracyclophane scaffold in which two aryl rings are tethered by both a 1, 8‐biphenylene unit and a O−P−O bridge. Suitable aryl substituents generate planar chirality. Their gold(I) complexes promote the cycloisomerization of prochiral nitrogen‐tethered dienynes to afford bicyclic derivatives with very high diastereoselectivity and up to 95 % ee (see scheme).